ANALISIS EFISIENSI DAN EFEKTIVITAS PENERIMAAN RETRIBUSI PASAR SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN PEKALONGAN TAHUN 2017-2021 - Anni Safitri; Fangela Myas Sari (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2022)
This study uses descriptive statistical methods. The analytical tool used is using the formula for efficiency, effectiveness, and market retribution contributions with 2017-2021 data. The examples used are Market Retribution Revenue Data, Market Levies Collection Cost Data, and Pekalongan Regency Original Regional Revenue (PAD) data obtained from the Industry & Trade Office and the Pekalongan Regency Regional Financial Management Agency.The results of this study indicate that the efficiency level of market retribution revenue in 2017-2021 is classified as very efficient with an average of 3.95%. The level of acceptance of market retribution in 2017-2021 is classified as less effective with an average acquisition of 82.07%. The contribution of market levies to Pekalongan Regency's original regional income (PAD) in 2017-2021 is classified as less large with an average of 1.54%.